Revisiting Native Grammar Through L2 Theories: Knowledge And Processing of Null and Overt Subject Pronouns in Turkish - Cinar, Oktay (Nesne-psikoloji Dergisi, 2024)
This study investigates the interpretative and processing mechanisms of null and overt subject pronouns at the syntax-discourse interface among native Turkish speakers. The research focuses on whether challenges in L2 acquisition of subject pronoun distribution are also observed in the properties of native grammars, guided by the Interface Hypothesis (IH) and the Pragmatic Principles Violation Hypothesis (PPVH). Results from the acceptability judgement task indicate that native Turkish speakers do not uniformly interpret null and overt subjects; overt subjects are often pragmatically overused in contexts requiring topic continuity. However, the findings from the self-paced reading task showed no significant processing differences between felicitous and infelicitous uses of subject pronouns, suggesting that native speakers might not actively penalize grammatical infelicities during realtime processing. These results suggest that issues traditionally associated with L2 acquisition might also be intrinsic to native language behavior. The study calls for further cross-linguistic research to determine if these findings are specific to Turkish or part of a broader pattern in null subject languages.